Thermal conductivity of nonunitary triplet superconductors: application to UTe2 - Mishra, Vivek; Wang, Ge; Hirschfeld, P. J. (Frontiers in Physics, 2024)
There is considerable evidence that the heavy fermion material UTe 2 is a spin-triplet superconductor, possibly manifesting time-reversal symmetry breaking, as measured by Kerr effect and muon spin resonance experiments below the critical temperature, in some samples.Such signals can arise due to a chiral orbital state, or possible nonunitary pairing. Although experiments at low T appear to be consistent with point nodes in the spectral gap, the detailed form of the order parameter and even the nodal positions are not yet determined. Thermal conductivity measurements can extend to quite low temperatures, and by varying the heat current direction should be able to provide information on the order parameter structure. Here we derive a general expression for the thermal conductivity of a spin triplet superconductor, and use it to compare the low-temperature behavior of various states proposed for UTe 2 .